2019
DOI: 10.32799/ijih.v14i2.31945
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Youth Development through Sport and Physical Activity: Sharing Voices, Stories, and Experiences

Abstract: Recent research has highlighted the cognitive, physical, emotional, and spiritual benefits of sport and physical activity participation for Indigenous youth (McHugh, Coppola, & Sinclair, 2013; Hanna, 2009; Lavallée, 2007). Despite the importance of Indigenous peoples participating in sport and physical activity (e.g., Forsyth & Giles, 2013), the meaning of youth development in this context is not well understood. The purpose of this research was to understand Indigenous youth development within the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Seven articles ( n = 7/32; 22%) included a visual or symbolic conceptualization to guide data analysis (Bruner et al, 2019; Carter et al, 2017; Galway et al, 2022; Marsh et al, 2015; Rowan et al, 2015; Sylliboy, 2021; VanEvery et al, 2022). Bruner et al (2019), used Indigenous Symbolic Analysis as described by McNiff (1998) to guide data analysis. The authors identified this as an Indigenous approach to better represent the experience shared by Indigenous participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven articles ( n = 7/32; 22%) included a visual or symbolic conceptualization to guide data analysis (Bruner et al, 2019; Carter et al, 2017; Galway et al, 2022; Marsh et al, 2015; Rowan et al, 2015; Sylliboy, 2021; VanEvery et al, 2022). Bruner et al (2019), used Indigenous Symbolic Analysis as described by McNiff (1998) to guide data analysis. The authors identified this as an Indigenous approach to better represent the experience shared by Indigenous participants.…”
Section: Resultsmentioning
confidence: 99%
“…According to Marsh et al (2015), transparency and member checking is grounded in the Two-Eyed Seeing Indigenous decolonizing approach and Aboriginal research ethics/protocol. The second most common strategy to involve Indigenous community members was the creation of an Indigenous advisory group which represented under half ( n = 12/32; 38%) of the articles (Bruner et al, 2019; Cabrera et al, 2015; Carter et al, 2017; Hall et al, 2015; Hatala et al, 2020; Jacklin et al, 2020; Marsh et al, 2015; Martin et al, 2017, 2018; Rowan et al, 2015; Tarasuk et al, 2021; Wekerie et al, 2022). Involvement of an Indigenous community member with the coding and analysis process was the next most common strategy ( n = 9/32; 28%) (Bruner et al, 2019; Galway et al, 2022; Hunt et al, 2018; Latimer et al, 2020; Marsh et al, 2015; VanEvery et al, 2022; Vorobyova et al, 2022; Ward et al, 2023; Wright et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 ). It may also strengthen resiliency and instil values such as honesty, courage and respect which have been reported to positively impact the holistic sense of SEWB in Indigenous people ( Bruner et al, 2019 , Cargo et al, 2007 , Lavallée and Lévesque, 2013 ). Research by Dalton et al (2015) also found similar positive associations between exercise and mental wellbeing within an Australian setting.…”
Section: Introductionmentioning
confidence: 99%